Perishability and market power in Nepalese food crop production - Thomas Kopp; Ashok K. Mishra (Journal of Agricultural Economics, 2021)
This study provides empirical evidence for the relation between perishability in vertically coordinated supply chains and the market power exercised over smallholders in Nepal. Using survey data from small-scale farms of tomatoes, ginger, high-yielding variety paddy seeds, and lentils, we demonstrate how varying levels of perishability affect the degree of market power exercised by contractors and in cooperative farming. We show how much value-added is diverted from farmers, compared to the benchmark set by the least perishable good. Results indicate that more perishable crops are subject to a greater degree of market power. A subsequent scenario analysis reveals that the redistributive effects of market power based on crop perishability are substantial: smallholders' farm profitability increase by 18% as crop perishability is reduced by 50%. We conclude by discussing policy measures to reduce power imbalances due to crop perishability.
Keywords: 630; market power; Nepal; perishability; storability